Analysis of Attitude, Motivation, Knowledge and Lifestyle of the Consumers in Bandung Who Shop through Instagram - Nina Maharani; Lufthia Sevriana (The Winners, 2017)
The research purposes were (1) to find out the most dominant variable (either it was attitude, motivation, knowledge or lifestyle) that had influenced consumers to do shopping through Instagram, and (2) to give a contribution to the marketing strategy for seller/reseller who run an online business through Instagram. The method of this research was a survey with 154 people as the sample. The sample selection technique of this research was accidental sampling. Data analysis of this research used a confirmatory factor analysis. It finds that the most dominant variable that influences consumers’ purchasing decision through Instagram is consumers’ knowledge. By knowing what the most dominant variable is, this study proposes the most appropriate marketing strategy base to the promotion of a brand in Instagram. The segmentation bases that can be used in Instagram are gender, social class, age, and lifestyle. The marketing target includes women of middle social class ranging from 15 until 25 years old. Most products sold in Instagram are related to fashion, accessories, and gadget.